2015
DOI: 10.2478/asorg-2014-0002
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of (R)-convolutamydine A involving in situ chiral organocatalyst formation

Abstract: The application of a convenient one-pot synthetic strategy, utilizing an in situ formed organocatalyst, to the enantioselective synthesis of anti-leukaemia agent (R)-convolutamydine A has been demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…It was found that neat reaction performed in dry acetone had significantly lower yields compared to that carried out in wet acetone (Table 1, entry 3 and Table 2, entry 1). The presence of water in organocatalysed reactions of isatin with acetone has been reported to significantly influence the product yield and enantioselectivity [20,51] . By adding 10 equivalents of water to the L‐leucinol catalysed isatin reaction in anhydrous acetone, dramatic improvements (93 % yield and 94 % ee , see Table 2, entry 3) were observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that neat reaction performed in dry acetone had significantly lower yields compared to that carried out in wet acetone (Table 1, entry 3 and Table 2, entry 1). The presence of water in organocatalysed reactions of isatin with acetone has been reported to significantly influence the product yield and enantioselectivity [20,51] . By adding 10 equivalents of water to the L‐leucinol catalysed isatin reaction in anhydrous acetone, dramatic improvements (93 % yield and 94 % ee , see Table 2, entry 3) were observed.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most efficient ways for accessing this desirable scaffold is via organocatalysed aldol condensation of a ketone with an isatin derivative. While there have been several organocatalysts reported for this reaction, the leucinol catalysed cross aldol reaction of isatin with acetone in CH 2 Cl 2 solvent reported by Malkov and co‐workers [19–21] provided arguably one of the most efficient route for accessing enantiopure 3‐substituted‐3‐hydroxyoxindole derivatives at ambient temperature. In their work, they demonstrated leucinol to be a simple and cost‐effective organic catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…[13] The research group led by Tsogoeva delved into the use of in situ generated organocatalysts for the aldol reaction, generating amino alcohol organocatalysts IV in situ from corresponding amino acids L-Val or L-Leu through BH 3 -mediated reduction. [14] This approach, under mild conditions, facilitated the synthesis of the antileukemia agent (R)-convolutamydine A in a 95 % yield and with an 85 % ee (Scheme 1).…”
Section: A Organocatalytic Reactions Using Prolinamides Peptides Prim...mentioning
confidence: 99%
“…Further exploration led to the catalysis by N ‐(2‐thiophenesulfonyl) prolinamide III , which produced ( S )‐convolutamydine A with an impressive 97 % ee in the aldol reaction of 4,6‐dibromoisatin ( 1 ) with acetone ( 2 ) [13] . The research group led by Tsogoeva delved into the use of in situ generated organocatalysts for the aldol reaction, generating amino alcohol organocatalysts IV in situ from corresponding amino acids L‐Val or L‐Leu through BH 3 ‐mediated reduction [14] . This approach, under mild conditions, facilitated the synthesis of the antileukemia agent ( R )‐convolutamydine A in a 95 % yield and with an 85 % ee (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Tsogoeva and co-workers reported the amino alcohol-catalyzed one-pot enantioselective synthesis of antileukaemia agent ( R )-convolutamydine A in 95% yield and with 85% ee under mild conditions ( Scheme 23 ) [ 39 ]. Notably, the amino alcohol catalysts were generated in situ from the corresponding amino acids L-Leu or L-Val through the BH 3 -mediated reduction, making the multi-step synthesis more efficient and environmentally friendly.…”
Section: Reviewmentioning
confidence: 99%